Raspberry Pi for kids for dummies - Wentk, Richard (John Wiley &​ Sons, Inc., 2015)
Getting acquainted with your Raspberry Pi has never been sweeter Raspberry Pi For Kids For Dummies makes it easy for kids to set-up, operate, and troubleshoot like a Pi pro! Introducing you to Pi through a series of entertaining and inspiring projects, this handy, step-by-step guide shows you how to write computer games, build websites, make art and music, create electronic projects, and much more! From downloading the operating system and setting up your Raspberry Pi to creating art in Tux Paint and designing games with Scratch, everything you need to have fun with Pi is inside! Raspberry Pi For Kids For Dummies leaves the confusing tech talk behind and explains in plain English how to unleash all the cool possibilities of Pi, like playing Minecraft in Python, using HTML to make a website, managing and customizing your Raspberry Pi, playing music with Sonic Pi, and understanding and playing with the GPIO. * Teaches the basics of Raspberry Pi in a simple and thorough approach * Shows you how to zoom around Pi, all while learning valuable programming skills * Offers tons of exciting projects to keep you engaged as you learn * Includes instruction on everything you need to troubleshoot Raspberry Pi If you're aspiring computer programmer age 8-18 and want to start having fun with Pi, look no further than Raspberry Pi For Kids For Dummies.